The incredible vegetable group - Aboff, Marcie; Poling, Kyle (Mankato, Minn Capstone Press, 2012)
You re hungry. What should you eat? With MyPyramid and Healthy Eating, it s easy to decide. Find out WHERE OUR VEGETABLES COME FROM, WHAT NUTRIENTS WE GET FROM VEGETABLES, AND how many servings you need EACH day
Comic Strips
a gift from book africa
1 2 13 15
Keywords: Comic books, strips, etc -- Nutrition; Graphic novels; Nutrition